A model for the simulation of the chill block melt spinning (CBMS) process using OpenFOAM® (2020)
This work shows the results of a numerical model developed to simulate the CBMS technique for the production of the Fe78Si9B13 metallic magnetic ribbons for application in electronics. The model proposes a numerical approximation to a Vogel-Fulcher-Tammann (VFT) expression as a method in the solidification process. This approximation is introduced into the “compressibleInterFoam” routine, included in the OpenFOAM® suite, originally developed for the simulation of two immiscible, non-isothermal and compressible fluids. This routine solves, the phase fraction transport using the Volume of Fluids (VOF) approach. The boundary conditions imposed in the model were experimentally validated by digital image analysis with a high-speed camera at 5602 fps for the determination of the temperature profiles. The phase change is represented as a growth of several orders of magnitude of the alloy viscosity (μ) as the temperature (T) decreases, reaching solidification around the crystallization temperature (Tg). Also, we establish the condition of initial stability of CBMS process (R > 1.5) for Peclet numbers close to 400, and the validity up to limits of rotation in the wheel close to 40 m s−1. The proposed methodology is validated with previous work. Encouraging results show that the solution of the CBMS process can be adequately simulated with the proposed approach. © 2019 Elsevier Masson SAS